Strong tripled fixed points under a new class of F-contractive mappings with supportive applications - Hasanen A. Hammad; Doha A. Kattan (AIMS Mathematics)
A significant advancement in the field of fixed point theory is presented in this manuscript. The existence and uniqueness of strong tripled coincidence points for F-contractive mappings in metric spaces were investigated. An extension of this analysis to multivalued F-contractive mappings was provided, establishing the existence of tripled fixed points within this generalized setting. Existing findings in the literature were generalized and refined by these results, offering a more comprehensive understanding of fixed point phenomena. Furthermore, the practical applicability of these theoretical contributions was demonstrated through the study of solutions to various forms of nonlinear integral equations and integral-type inequalities.